2006
DOI: 10.1007/s10620-005-9037-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effectiveness of Azathioprine in IBD Beyond 4 Years: A European Multicenter Study in 1176 Patients

Abstract: In Crohn's disease the optimal duration of azathioprine treatment is still controversial and for ulcerative colitis only limited data are available to support its efficacy. Charts of 1176 patients with IBD from 16 European centers were analyzed. Flare incidences and steroid dosages were assessed for the time before and during treatment and after discontinuation. Within the first 4 years, azathioprine suppressed flare incidence and steroid consumption in both diseases (P < 0.001). While in CD discontinuation af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 18 publications
1
44
0
1
Order By: Relevance
“…A systematic review ( 235 ) and meta-analysis ( 236 ) concluded that azathioprine is a modestly eff ective ( 236 ) maintenance therapy for patients who have failed or cannot tolerate mesalamine or sulfasalazine, and for patients who require repeated courses of steroids and this benefi t should be considered in the context of the potential for adverse events from the thiopurines ( 235 ). Similarly, uncontrolled retrospective data from 105 patients treated with continued long-term 6-MP ( 234 ), from 351 patients treated with long-term azathioprine ( 200 ) in the United States, and from 298 patients treated with azathioprine in multiple centers in Europe ( 186 ) appear to confi rm the effi cacy of these agents continued long-term in maintaining remissions of UC ( 237 ).…”
Section: The Patient With Severe Colitis Refractory To Maximal Oral Tmentioning
confidence: 98%
See 1 more Smart Citation
“…A systematic review ( 235 ) and meta-analysis ( 236 ) concluded that azathioprine is a modestly eff ective ( 236 ) maintenance therapy for patients who have failed or cannot tolerate mesalamine or sulfasalazine, and for patients who require repeated courses of steroids and this benefi t should be considered in the context of the potential for adverse events from the thiopurines ( 235 ). Similarly, uncontrolled retrospective data from 105 patients treated with continued long-term 6-MP ( 234 ), from 351 patients treated with long-term azathioprine ( 200 ) in the United States, and from 298 patients treated with azathioprine in multiple centers in Europe ( 186 ) appear to confi rm the effi cacy of these agents continued long-term in maintaining remissions of UC ( 237 ).…”
Section: The Patient With Severe Colitis Refractory To Maximal Oral Tmentioning
confidence: 98%
“…Randomized controlled trials with a relatively small number of enrolled patients ( 183,184 ) as well as uncontrolled trials ( 185,186 ) of azathioprine in doses up to 1.5 -2.5 mg / kg per day have shown its eff ectiveness in patients who do not respond to, or cannot be weaned from steroids ( 187 ). Th eir primary benefi t is in the steroidsparing eff ect, rather than as an agent to be used as monotherapy to induce remission.…”
Section: Thiopurinesmentioning
confidence: 99%
“…In the multicenter study conducted in European countries, prolongation of treatment duration showed the additional benefit of decreased rates of flares, which could be treated with lower doses of corticosteroids (8). Among these studies, the longest reported AZA use among UC patients was as long as 16 years without any significant side effect.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7] After this regimen fails, corticosteroids and immunosuppressants are initiated. [8][9][10][11][12][13][14] Finally, at the top of the pyramid, anti-TNF is currently widely established for both CD and UC patients. [15][16][17][18] Patients are often treated with a combination of immunosuppressants.…”
Section: Introductionmentioning
confidence: 99%